An adventure in statistics : the reality enigma - Field, Andy P.; Iles, James (New Delhi Sage, 2016)
Providing a vibrant alternative to the dullness of many typical offerings, the book assumes no previous statistics knowledge nor does it require the use of data analysis software. It covers the material you would expect for an introductory level statistics course and presents strong foundations for understanding classical and Bayesian approaches to data analysis. Illustrated with stunning graphic-novel style art and featuring Socratic dialogue, the story captivates readers as it introduces them to concepts, eliminating potential statistics anxiety.
Keywords: Statistics -- Textbooks; Mathematics; Statistics; Mathematics